Tattoos and Piercings: Increasingly Accepted but Still Risky. Issue 2 (March 2018) - Beal, Judy A.
Abstract : Our pediatric nursing expert, Dr. Beal, discusses the recent clinical report from the American Academy of Pediatrics on Adolescent and Young Adult Tattooing, Piercing, and Scarification. As these practices are becoming more common, it is important for pediatrics nurses to have up-to-date knowledge so they can assist in guiding adolescents and parents.